A contemporary sense of existentialism. Issue 3 (2nd September 2016) - Wardle, Darryl
Abstract : Philosophical existentialism has sought to understand the nature of human existence and the possible meaning(s) that might be made thereof. For the noteworthy existentialist Jean-Paul Sartre, the meaning of life cannot be said to subsist somewhere beyond the province of individual human existence, since meaning is born of a fundamental freedom which inheres in human consciousness. From a more contemporary poststructuralist philosophical perspective, however, one might argue that Sartre's individualist conception of existential meaning in Being and Nothingness remains fettered to an order of signification reliant upon a vestigial "metaphysics of presence", where the presence of the signified has simply been displaced from the transcendental domain to immanent human subjectivity. This is potentially problematic insofar as such an order of meaning qua signification is destined to suspend meaning at a perpetually deferred distance; and concomitantly, human existential meaning remains interminably frustrated. However, using the contemporary philosophical insights of Jean-Luc Nancy, it can be argued that a contemporary (re) conceptualisation of existentialist thought might allow existentialism to liberate itself from a ceaselessly suspended signification of meaning, specifically by arguing for a means-to-meaning(s) always already manifest(ing) between human beings oriented towards the contemporary world as a shared space of sense .